Effect of Atmospheric Plasma Treatment on Pad-dyeing of Natural Dyes on Wool (Journal of Fiber Bioengineering and Informatics, 2018)
Plasma treatment is an emerging surface modification technique that alters dye uptake of wool withoutusing chemicals or water for pre-treatment. Padding is an established continuous dyeing technique knownfor its efficient use of water, time and energy. This study combined these two techniques for colourationof wool fabric using two natural dyes derived from the Acacia plant family. The investigation focused onthe effects of plasma treatment and obtaining unique patterning effects. Helium (100%) and a mixtureof helium and nitrogen (95%/5%) were used as the plasma gases under atmospheric conditions. Plasmatreated wool fabric was padded with the above natural dyes. Copper sulphate and ferrous sulphate wereapplied on the dyed fabric as mordant yielding neutral shades of beige and grey respectively. Up toa 30% enhancement of dye adsorption on plasma treated wool substrate was observed as compared tountreated sample for both gases used. This higher adsorption indicates the hydrophilic character of thenatural dyes used. Key performance parameters such as fastness to washing, rubbing and light weretested and found to be satisfactory. A single process tone-on-tone pattern was achieved by controllingthe plasma exposure of treated area. This study concluded that a merger of natural dyes with modernplasma treatment and padding techniques for wool colouration was feasible.
Keywords: Acacia Natural Dye; Atmospheric Plasma Treatment; Padding; Mordant; Wool Fabric